Quasi-"In Situ" Analysis of the Reactive Liquid-Solid Interface during Magnesium Corrosion Using Cryo-Atom Probe Tomography - Schwarz, Tim M (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.